FOREIGN LANGUAGE TEACHING AND METHODS USED DURING THE LANGUAGE LESSONS - Musulmonov Shabon Bahodir o’g’li (European Journal of Humanities and Educational Advancements, 2023)
Foreign language teaching has a very high position in education system of the country. As the world is now developed and globalized, the probability to talk and collaborate with speakers of distinct language has increased. This article discusses new guidelines into a curriculum, describes different methods and states what learning methods work best for language teaching, and the role of technological era